The Impact of Neonatal Methamphetamine on Spatial Learning and Memory in Adult Female Rats - Petrikova-Hrebickova, Ivana; Sevcikova, Maria; Šlamberová, Romana (Frontiers in Behavioral Neuroscience, 2021)
The present study was aimed at evaluating cognitive changes following neonatal methamphetamine exposure in combination with repeated treatment in adulthood of female Wistar rats. Pregnant dams and their pups were used in this study. One half of the offspring were treated indirectly via the breast milk of injected mothers, and the other half of pups were treated directly by methamphetamine injection. In the group with indirect exposure, mothers received methamphetamine (5 mg/ml/kg) or saline (1 ml/kg) between postnatal days (PD) 1–11. In the group with direct exposure, none of the mothers were treated. Instead, progeny were either: (1) treated with injected methamphetamine (5 mg/ml/kg); or (2) served as controls and received sham injections (no saline, just a needle stick) on PD 1–11. Learning ability and memory consolidation were tested on PD 70–90 in the Morris Water Maze (MWM) using three tests: Place Navigation Test, Probe Test, and Memory Recall Test. Adult female progeny were injected daily, after completion of the last trial of MWM tests, with saline or methamphetamine (1 mg/ml/kg). The effects of indirect/direct neonatal methamphetamine exposure combined with acute adult methamphetamine treatment on cognitive functions in female rats were compared. Statistical analyses showed that neonatal drug exposure worsened spatial learning and the ability to remember the position of a hidden platform. The study also demonstrated that direct methamphetamine exposure has a more significant impact on learning and memory than indirect exposure. The acute dose of the drug did not produce any changes in cognitive ability. Analyses of search strategies (thigmotaxis, scanning) used by females during the Place Navigation Test and Memory Recall Test confirmed all these results. Results from the present study suggested extensive deficits in learning skills and memory of female rats that may be linked to the negative impact of neonatal methamphetamine exposure.